2009
DOI: 10.1080/01443610802646892
|View full text |Cite
|
Sign up to set email alerts
|

Long-term epidural analgesia treatment in pre-eclamptic women: A preliminary trial

Abstract: Pre-eclampsia (PE) is a clinical pregnancy-related condition, characterised by an elevated blood pressure and proteinuria. The author treated selected cases of PE with long-term epidural analgesia (LTEA), that reduced labour pain and operated directly on the PE aetiopathogenesis, not on the symptoms. A total of 15 women with PE were hospitalised at 35-37 weeks of pregnancy, checked for blood pressure, liver and renal function, platelet count and had an epidural catheter inserted for a continuous administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Additionally, long-term epidural analgesia, including SUF, alleviates the labor pain in PE patients and immediately targets the pathogenesis of PE for operation [ 9 ]. Nevertheless, the latent mechanism of SUF targeting PE remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, long-term epidural analgesia, including SUF, alleviates the labor pain in PE patients and immediately targets the pathogenesis of PE for operation [ 9 ]. Nevertheless, the latent mechanism of SUF targeting PE remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…SUF reduces ropivacaine-stimulated apoptosis of umbilical cord mesenchymal stem cells via mediating miR-182-5p/BCL10/CYCS axis [ 8 ]. Emerging research has also reported that SUF cures PE in combination with other drugs like long-term epidural analgesia (LTEA), naloxone, and Clonidine [ 9 ]. Nevertheless, the action of SUF alone in PE and its latent mechanism remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Extended epidural analgesia has also been reported to be welltolerated for up to one week (Malvasi 2009).…”
Section: Cochrane Database Of Systematic Reviewsmentioning
confidence: 98%
“…When a catheter is placed into the epidural space, a continuous infusion can be maintained for several days, if needed. Epidural analgesia successfully has been used for postoperative analgesia, the treatment of back pain, chronic pain, and palliation of symptoms in terminal care (Ezhevskaia & Prusakova, 2012;Malvasi et al, 2009;Richter et al, 2002;Schulte et al, 2008). Evidence that use of epidural analgesia also enhances the recovery process would lead to wider adoption of this method and better quality of care for surgical patients (Fotiadis, Badvie, Weston, & Allen-Mersh, 2004;Yeh et al, 2005).…”
mentioning
confidence: 96%